Development of the referee anxiety scale in officiating football matches - Saifuddin Saifuddin; Nyak Amir; Sumaryanto Sumaryanto (Jurnal Cakrawala Pendidikan, 2022)
A referee’s important roles often lead to anxiety that affects the psychological stances in the decision-making while officiating a match. In this light, the present study aimed to develop a valid and reliable anxiety scale for football referees. The research and development method was applied in this study by involving 13 referees and 5 experts in the selection and determination of the details of the statement. The subjects of the tryout were 30 football referees in Aceh Province. The Football Referee Anxiety Scale (FRAS) is developed through the analysis of various anxiety instruments that have been developed, item selection, small scale, and large-scale tryouts, and factor analysis to test its validity and reliability. The results showed that the referee anxiety scale in a football match had high levels of validity and reliability. The scale comprised 51 questions in four dimensions, which consisted of 10 questions for the cognitive dimension, 17 for the affective dimension, 17 for the somatic dimension, and 7 for the motoric dimension. This scale could be used for the football referees at the regional and national levels. This referee anxiety scale could be refined through a test on a larger number of referees in the different match levels.